PD-1 inhibitor sintilimab treated patients with metastatic triple-negative breast cancer - Jia, Yan; Zhang, Jie; Shi, Yehui; Dong, Guolei; Guo, Xiaojing; Tong, Zhongsheng (Frontiers in Cell and Developmental Biology, 2024)
Purpose Triple-negative breast cancer (TNBC) is a highly challenging subtype due to a unique tumor microenvironment. Several evidence (IMpassion130 trial and KEYNOTE-355 trial) supported the therapeutic effect of the immune checkpoint inhibitor in TNBC. However, the efficacy and safety of the PD-1 inhibitor sintilimab in breast cancer (BC) has not been well-investigated. So the real-world data on sintilimab-treated patients with metastatic BC were collected and analyzed in this study. Methods The patients were eligible according to the requirements included: ages between 18 years and 75 years; recurrent or metastatic TNBC; measurable disease based on RECIST v1.1; no limitation on the prior systemic treatments; and ECOG performance status of 0–1. Patients received sintilimab 200 mg intravenously every 3 weeks until unacceptable toxicity or disease progression. Results From 1 June 2019 to 1 October 2022, 40 female patients (median age, 55.5 years) with metastatic TNBC (mTNBC) were enrolled into the study. The median prior lines of systemic therapy for mTNBC was three (range, 1–8), with 60% of cases receiving at least three lines of therapy for metastatic disease. The visceral or brain metastasis was detected in 40.4% or 9.6% of patients, respectively. The median duration of response was 2.8 months (range, 0.7–21.0), and the median number of sintilimab doses administered was 4 (range, 1–30). The ORR and DCR were 22.5% and 72.5%, separately. The median PFS was 3.5 months (range, 1.4–21.0), with a 6-month PFS rate of 15.0% (6/40). The median OS was 52.5 months (range, 9.0–247.0) as of data cut-off. Common adverse effects were acceptable, and fatigue, skin rash, and pruritus were the frequent toxicity observed. Two cases of grade 3 curable adverse events were considered to be treatment-related. PD-L1-positive tumor was found in 40% cases (4/10) of mTNBC. Although statistical difference was not reached, the trend was obvious. Patients with PD-L1-positive tumor gained better treatment response, while the TMB-high carrier received more benefits of PFS and OS. Conclusion In our study, preliminary evidence provided the anticancer activity and acceptable adverse effects of sintilimab administered every 3 weeks to pretreated patients with mTNBC. Sintilimab showed its efficacy and safety of immunotherapy for patients with advanced TNBC.